Smiselna uporaba ZPP v nepravdnem postopku - Ude, Lojze (LeXonomica, 2021)
Analogous application of the Civil Procedure Code in non-contentious civil procedures. Author discusses the analogous application of the rules of the Civil Procedure Code in the non-contentious civil procedure before Slovenian courts. He presents the genesis of the Art. 37 of the Slovenian Non-Contentious Procedure Act, gives an overview of the regulation of this issue in comparative law, explains the notion of »analogous application« of the rules of the Civil Procedure Code in the non-contentious civil procedure and presents the corresponding Slovenian case law. Author is of opinion that more procedural provisions should be included and defined in the non- contentious procedure and referrals to the Civil Procedure Code should be eliminated only if the jurisprudence would indicate that the courts, regardless to the general referring provision, do not apply the provisions of Civil Procedure Code and its institutes as defined in the Code. Povzetek. Avtor v prispevku obravnava smiselno uporabo določb Zakona o pravdnem postopku v nepravdnih postopkih v Sloveniji. Pri tem opisuje genezo nastanka določbe 37. člena Zakona o nepravdnem postopku, prikaže rešitve v primerjalnem pravu in razlaga pojem smiselne uporabe določb Zakona o pravdnem postopku v nepravdnih postopkih ter predstavi primere iz sodne prakse. Avtor je mnenja, da bi bilo treba v nepravdnem postopku opredeliti več procesnih določb in iz njega izločiti splošno sklicevanje na Zakon o pravdnem postopku le, če bi iz sodne prakse izhajalo, da sodišča pogosto kljub splošni napotitveni normi ne uporabljajo določb Zakona o pravdnem postopku oz. njegovih procesnih institutov, kot so v tem zakonu opredeljeni.